The Application of Nucleic Acid Probe–Based Fluorescent Sensing and Imaging in Cancer Diagnosis and Therapy - Huang, Ge; Su, Chen; Wang, Lijuan; Fei, Yanxia; Yang, Jinfeng (Frontiers in Chemistry, 2021)
It is well-known that cancer incidence and death rates have been growing, but the development of cancer theranostic and therapeutics has been a challenging work. Recently, nucleic acid probes-based fluorescent sensing and imaging have achieved remarkable improvements in a variety of cancer management, credited to their high sensitivity, good tolerance to interference, fast detection, and high versatility. Herein, nucleic acid probes-based fluorescent sensing and imaging are labeled with advanced fluorophores, which are essential for fast and sensitive detection of aberrant nucleic acids and other cancer-relevant molecules, consequently performing cancer early diagnostics and targeted treatment. In this review, we introduce the characteristics of nucleic acid probes, summarize the development of nucleic acid probes-based fluorescent sensing and imaging, and prominently elaborate their applications in cancer diagnostics and treatment. In discussion, some challenges and perspectives are elaborated in the field of nucleic acid probes-based fluorescent sensing and imaging.